Effect of gastric lavage with Hemostasis Powder® on upper gastrointestinal bleeding (Conversion of emergency endoscopy to elective endoscopy) - Seyed Mousal-Reza Hosseini; Malihe Dadgar Moghaddam; Samaneh YazdanPanah; Jamshid Vafaeimanesh (Babol University of Medical Sciences, 2020)
Background: From many years ago, gastric lavage has been one of the main pillars of the classic treatment for upper gastrointestinal bleeding (UGIB). The present study investigated the effect of gastric lavage with hemostatic powder on the UGIB complications. Methods: This clinical trial study was performed on 54 patients who referred to the emergency department during 2017-2018. The subjects were divided into two groups (n=27 per group). Gastric lavage with saline and hemostasis powder® was performed in the control and experimental groups, respectively. The patients' information was collected and analyzed using SPSS software Version. 18. The significance level was set to p<0.05%. Results: In this study,59.2% and 18.5% of the patients in the gastric lavage with Hemostasis Powder® and saline required no treatment during the early endoscopy, respectively (p=0.002). The duration of endoscopy was shorter in the experimental group (p=0.001), (4.83±8.04 hours vs.6.73±14.12 hours, respectively) (p=0.001). Moreover, the gastric lavage with Hemostasis Powder® significantly improved the quality of endoscopy .There was no difference between the two groups in terms of their need for blood transfusion (p=0.4). Conclusion: Gastric lavage with hemostasis powder® is a useful measure in the primary treatment of patients with UGIB and can convert emergency therapeutic endoscopy to diagnostic elective endoscopy with higher quality.